2021
DOI: 10.3390/rs13061175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multi-Source Soil Moisture Datasets over Central and Eastern Agricultural Area of China Using In Situ Monitoring Network

Abstract: Multi-source soil moisture (SM) products provide a vigorous tool for the estimation of soil moisture on a large scale, but it is crucial to carry out the evaluation of those products before further application. In the present work, an evaluation framework on multi-source SM datasets over central and eastern agricultural areas of China was firstly proposed, based on a dense in situ SM monitoring network of 838 stations from 11 July 2012 to 31 December 2017. Each station adopted the most accurate gravimetric met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…This study requires two sets of outputs: one set is the final predicted results ( ŷ) and the other set is the uncertainty standard deviation of the results ( σ). Therefore, the loss function used is shown in Equation (4).…”
Section: Loss Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study requires two sets of outputs: one set is the final predicted results ( ŷ) and the other set is the uncertainty standard deviation of the results ( σ). Therefore, the loss function used is shown in Equation (4).…”
Section: Loss Functionmentioning
confidence: 99%
“…Meteorological satellites enable more comprehensive monitoring of TC cloud patterns, structures, and dynamic changes, leading to more accurate intensity estimations. These satellites typically originate from meteorological satellite systems on different orbits or platforms, equipped with various satellite sensors or radiometers; hence, they are referred to as multi-source meteorological satellites [4].…”
Section: Introduction 1motivation and Backgroundmentioning
confidence: 99%
“…Advances in satellite technology, data processing, and petrophysics ensure that these techniques will be increasingly important in the future. Many studies have used satellite data, such as the Sentinel and Landsat series, to observe and predict soil properties such as pH [21,22], cation exchange capacity [22], soil organic carbon [22,23], soil organic matter [21,24], clay content [21,22,24], salinity [25], and soil water content estimation [26][27][28][29][30][31][32]. Reference [24] showed that using Sentinel-2 satellite data to identify differences in soil properties can guide on-ground soil sampling and significantly reduce the time and cost of conventional sampling efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focus mainly on the assessment of soil moisture or soil water content. Currently, a number of systems based on active and passive radar remote sensing and synthetic multisource datasets are available (see [31,32]). A major drawback of these data is the very small scale resolution, which is completely inadequate for assessing individual soil blocks.…”
Section: Introductionmentioning
confidence: 99%